Errors in Organizations. - Hofmann, David A. (Taylor & Francis, 2011)
Despite the importance and prevalence of errors in organizations, there has been no attempt within the field of Industrial and Organizational psychology to create a single source that summarizes what we know regarding errors in organizations and provides a focused effort toward identifying future directions of research. This volume answers that need and provides contributions by researchers who have conducted a considerable amount of research on error occurring in the work context. Students, academics and practitioners in a wide range of disciplines, i.e., industrial organizational psychology.